(untitled) (Research, Society and Development, 2023)
Introduction: Cardiac lesions are frequently observed in individuals diagnosed with COVID-19. However, in most cases patients are asymptomatic and may manifest increased blood troponin levels, myocardial dysfunction and electrocardiographic abnormalities. The present study aims to bibliographically review acute cardiac manifestations in adults diagnosed with SARS-CoV-2. Methodology: Integrative literature review, with a survey in the databases: PubMed, Scielo and UpToDate. The inclusion and exclusion criteria were applied, totaling a selection of 60 articles to compose the study. Results and discussion: In most cases, the clinical symptoms of patients with acute cardiac injury are compatible with the typical symptoms of COVID-19. Heart diseases are diagnosed through laboratory tests, electrocardiograms, or imaging. In relation to acute coronary syndrome, acute myocardial infarction is caused due to the incompatibility between oxygen supply and demand in most cases. Reports describing suspected myocarditis have been published, however, to date, the diagnosis of viral myocarditis directly related to COVID-19 has not been confirmed. Heart failure can be precipitated by SARS-CoV-2 in patients with previously known or undiagnosed heart disease. The highlighted disorder is hypoxia-related respiratory failure resulting in cardiogenic shock. Conclusion: Cardiac lesions related to COVID-19 commonly present asymptomatically. Early diagnosis is extremely important due to the increase in mortality rates. Studies seeking to confirm viral myocarditis due to COVID-19 are encouraged.